CONTROLE DE PLANTAS DANINHAS E SELETIVIDADE DE HERBICIDAS NA CULTURA DO GIRASSOL (ð˜ð˜¦ð˜ð˜ªð˜¢ð˜¯ð˜µð˜©ð˜¶ð˜´ ð˜¢ð˜¯ð˜¯ð˜¶ð˜´ L.) - Deuber, Robert; Machado, Pedro R.; Mathes, Luiz A. F. (REVISTA DE AGRICULTURA, 2020)
CONTROLE DE PLANTAS DANINHAS E SELETIVIDADE DE HERBICIDAS NA CULTURA DO GIRASSOL (ð˜ð˜¦ð˜ð˜ªð˜¢ð˜¯ð˜µð˜©ð˜¶ð˜´ ð˜¢ð˜¯ð˜¯ð˜¶ð˜´ L.)